An extended mixture model for the simultaneous treatment of small-scale and large-scale interfaces - Marquez Damian, Santiago (2014)
The aim of this work is to present a new model based on the volume of fluid method and the algebraic slip mixture model in order to solve multiphase gas?fluid flows with different interface scales and the transition among them. The interface scale is characterized by a measure of the grid, which acts as a geometrical filter and is related with the accuracy in the solution; in this sense, the presented coupled model allows to reduce the grid requirements for a given accuracy. With this objective in mind, a generalization of the algebraic slip mixture model is proposed to solve problems involving small-scale and large-scale interfaces in an unified framework taking special care in preserving the conservativeness of the fluxes. This model is implemented using the OpenFOAMr libraries to generate a tool capable of solving large problems on high-performance computing facilities. Several examples are solved as a validation for the presented model, including new quantitative measurements to assess the advantages of the method.